Reductions in carotid chemoreceptor activity with low‐dose dopamine improves baroreflex control of heart rate during hypoxia in humans - Mozer, Michael T. (Physiol Rep, 2016)
The purpose of the present investigation was to examine the contribution of the carotid body chemoreceptors to changes in baroreflex control of heart rate with exposure to hypoxia. We hypothesized spontaneous cardiac baroreflex sensitivity (scBRS) would be reduced with hypoxia and this effect would be blunted when carotid chemoreceptor activity was reduced with low‐dose dopamine. Fifteen healthy adults (11 M/4 F) completed two visits randomized to intravenous dopamine or placebo (saline). On each visit, subjects were exposed to 5‐min normoxia (~99% S(p)O(2)), followed by 5‐min hypoxia (~84% S(p)O(2)). Blood pressure (intra‐arterial catheter) and heart rate (ECG) were measured continuously and scBRS was assessed by spectrum and sequence methodologies. scBRS was reduced with hypoxia (P < 0.01). Using the spectrum analysis approach, the fall in scBRS with hypoxia was attenuated with infusion of low‐dose dopamine (P < 0.01). The decrease in baroreflex sensitivity to rising pressures (scBRS “up‐up”) was also attenuated with low‐dose dopamine (P < 0.05). However, dopamine did not attenuate the decrease in baroreflex sensitivity to falling pressures (scBRS “down‐down”; P > 0.05). Present findings are consistent with a reduction in scBRS with systemic hypoxia. Furthermore, we show this effect is partially mediated by the carotid body chemoreceptors, given the fall in scBRS is attenuated when activity of the chemoreceptors is reduced with low‐dose dopamine. However, the improvement in scBRS with dopamine appears to be specific to rising blood pressures. These results may have important implications for impairments in baroreflex function common in disease states of acute and/or chronic hypoxemia, as well as the experimental use of dopamine to assess such changes.